Revealing Hydrogen Bond Effect in Rechargeable Aqueous Zinc‐Organic Batteries - Guo, Jun; Du, Jia‐Yi; Liu, Wan‐Qiang; Huang, Gang; Zhang, Xin‐Bo (Angewandte Chemie International Edition, 2024)
The surrounding hydrogen bond (H‐bond) interaction around the active sites plays indispensable functions in enabling the organic electrode materials (OEMs) to fulfill their roles as ion reservoirs in aqueous zinc‐organic batteries (ZOBs). Despite important, there are still no works could fully shed its real effects light on. Herein, quinone‐based small molecules with a H‐bond evolution model has been rationally selected to disclose the regulation and equilibration of H‐bond interaction between OEMs, and OEM and the electrolyte. It has been found that only a suitable H‐bond interaction could make the OEMs fully liberate their potential performance. Accordingly, the 2,5‐diaminocyclohexa‐2,5‐diene‐1,4‐dione (DABQ) with elaborately designed H‐bond structure exhibits a capacity of 193.3 mAh g−1 at a record‐high mass loading of 66.2 mg cm−2 and 100 % capacity retention after 1500 cycles at 5 A g−1. In addition, the DABQ//Zn battery also possesses air‐rechargeable ability by utilizing the chemistry redox of proton. Our results put forward a specific pathway to precise utilization of H‐bond to liberate the performance of OEMs. A series of quinone‐based small molecules with progressive hydrogen bond (H‐bond) numbers has been rationally designed to reveal the real effects of H‐bond on the electrochemical performance of organic electrode materials (OEMs) in rechargeable aqueous zinc‐organic batteries (ZOBs). The appropriate number of H‐bonds in OEM improves its structure stability and utilization of active sites and reduces the battery polarization, contributing to the construction of high‐performance ZOBs.